Effect of drying methods on the structure and properties of bacterial nanocellulose/MoS2 hybrid gel membranes and sphere-like particles for enhanced adsorption and photocatalytic applications - Marchiori, Leonardo [UNESP]; Santos, Leonardo Souza; Schuler, Thiago; Bernardes, Joseane Caroline; Mattos, Bianca Oliveira; Onishi, Bruno Seiki Domingos [UNESP]; Bortoletto-Santos, Ricardo; Rodrigues-Filho, Ubirajara Pereira; Domeneguetti, Rafael Romano [UNESP]; Ullah, Sajjad; Rambo, Carlos Renato; Ferreira-Neto, Elias Paiva; et al. (Springer Nature, 2024)
Bacterial nanocellulose hydrogels offer a versatile platform and promising porous support for the integration of inorganic photoactive nanostructures, enabling the design of functional hybrid and nanocomposite materials for water treatment and purification. However, the impact of different drying methods on the resulting hybrid gels needs to be investigated to optimize their photocatalytic and adsorptive performance. In this study, we present the preparation of hybrid BC/MoS2 membranes and sphere-like particles through the exploration of biosynthesis routes and hydrothermal modification. We systematically evaluated the effects of conventional heat drying (HD), freeze-drying (FD), and CO2 supercritical drying (SCD) on the structural and textural properties of pristine BC and hybrid BC/MoS2 membranes and sphere-like particles. The prepared materials were characterized using SEM, XRD, and N2 physisorption analysis. Material characterization revealed that hydrothermally grown semiconductor MoS2 nanosheets are successfully incorporated along the BC nanofibrils, while the BC scaffold maintains its open porous structure in SCD-dried membranes and sphere-like particles. Both SCD and FD methods effectively preserved the pore structure of membranes, resulting in materials with high specific surface area and pore volume. Conversely, drying the membranes using the heat drying (HD) method led to pore collapse and a drastic decrease in surface area. However, the FD method could not produce crack-free membranes. Among the sphere-like particle samples, only the SCD method was capable of producing materials with a high surface area and an open porous structure. Prepared SCD-dried BC/MoS2 hybrid aerogel sphere-like particles exhibited high adsorption capacity towards MB dye and Pb2+ contaminants, while SCD-dried hybrid membranes were explored for adsorptive filtration and for in-flow photo-assisted water purification. This study underscores the crucial role of drying methods in the preparation of nanocellulose-based hybrid and nanocomposite materials for water purification purposes. Graphical Abstract: (Figure presented.)
Keywords: Aerogel; Drying; MoS2; Nanocellulose; Photocatalysis